2002
DOI: 10.1074/jbc.m111290200
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Cryptic Domains in the α1-chain of Laminin-1 by Elastase Stimulates Macrophages Urokinase and Matrix Metalloproteinase-9 Expression

Abstract: Degradation of the extracellular matrix leads to the release of fragments, which elicit biological responses distinct from intact molecules. We have reported that ␣1:Ser 2091 -Arg 2108 , a peptide derived from the ␣1-chain of laminin-1, triggers protein kinase C-dependent activation of MAPK erk1/2 , leading to the up-regulation of macrophage urokinase type plasminogen activator and matrix metalloproteinase (MMP)-9 expression. Since intact laminin-1 failed to trigger these events, we hypothesized that ␣1:Ser 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 56 publications
(45 reference statements)
3
34
0
Order By: Relevance
“…In studies reported here, the activation of MAP-K erk1/2 was shown to be required for the up-regulation of the proteinase expression of macrophages induced by adhesion to SMC-ECM. These data confirm our earlier studies examining the role of MAPK erk1/2 in the induction of proteinase expression by synthetic ␣1-chain laminin peptides and laminin-1 fragments (42,43).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In studies reported here, the activation of MAP-K erk1/2 was shown to be required for the up-regulation of the proteinase expression of macrophages induced by adhesion to SMC-ECM. These data confirm our earlier studies examining the role of MAPK erk1/2 in the induction of proteinase expression by synthetic ␣1-chain laminin peptides and laminin-1 fragments (42,43).…”
Section: Discussionsupporting
confidence: 92%
“…1B). As expected, conditioned media derived from thioglycollateelicited macrophages contained increased levels of uPA, MMP-9, and MMP-2 relative to resident cells (9,43,48). When elicited macrophages were cultured on ECM, their expression of uPA and MMP-9 activities was further increased.…”
Section: Smc-ecm Stimulates Upa and Mmp-9 Expression Bysupporting
confidence: 73%
See 2 more Smart Citations
“…For example, cleavage of laminin-5, one of the ECM components that promotes stable cell attachment, by MMP-2 or MT1-MMP generates a proteolytic g2-chain fragment which promotes migration of human breast epithelial cells (Giannelli et al, 1997;Koshikawa et al, 2000). In addition, an a1-chain fragment generated by elastase proteolysis of laminin-1 has been shown to play a role in regulation of the macrophage degradative phenotype and in tissue remodeling (Khan et al, 2002). Note that the ECM fragments derived by MMP cleavage can also act as pro-angiogenic molecules, for example, the trimeric NC1 domain of collagen XVIII induces endothelial cell migration involved in angiogenesis (Kuo et al, 2001).…”
Section: Production Of Functional Fragmentsmentioning
confidence: 99%